IMPLEMENTASI MODEL KEPEMIMPINAN PENDIDIKAN ISLAM - Wahyudi, Kacung (Reflektika, 2021)
This article attempts to examine in detail about the leadership model of Islamic education. This research is a literature study that takes its main source from the literature relevant to the theme. The results of the analysis state that there are several models of Islamic leadership, including: autocratic, democratic, pseudo-democratic, laissez faire, militaristic, charismatic, populist and administrative. Each model has characteristics to distinguish and determine the leadership model used by a leader. However, in certain situations and conditions, leaders do not always apply one of the models of Islamic education leadership in achieving the goals of Islamic education to the fullest. Therefore, it is also necessary to observe approaches in leadership, namely the nature, behavior and situational or contingency approaches. This leadership approach also has a significant role in the success of achieving the goals of Islamic education.